In vitro and in vivo characterization of the bifunctional μ- and δ- opioid receptors ligand MCRT on mouse gastrointestinal motility. (April 2019) - He, Chunbo; Li, Hailan; Zhang, Jing; Zhou, Lanxia; Dong, Shouliang
Abstract: Background: Chimeric opioid MCRT was a novel multi-target ligand based on morphiceptin and PFRTic-NH2, and produced potent analgesia (ED50 = 0.03 nmol/mouse) with less upper gastrointestinal dysmotility. In this study, we sought to perform the tests to evaluate the pharmacological effects of MCRT on distal colon motility and defecation function. Moreover, opioid receptor antagonists and neuropeptide FF (NPFF) receptor antagonists were utilized to explore the mechanisms. Methods: Isolated mouse colon bioassay and colonic bead expulsion were to characterize MCRT-induced inhibition of colonic motility in vitro and in vivo, respectively. Fecal pellet output was to evaluate the defecation function. Results: (1) In vitro, MCRT increased colonic contraction via μ- and δ- opioid receptors (MOR and DOR). (2) In vivo, MCRT delayed colonic bead expulsion (ED50 = 1.1 nmol/mouse) independent of opioid and NPFF receptors. (3) In vivo, MCRT inhibited fecal number (ED50 = 1.43 nmol/mouse) and dry weight (ED50 = 1.63 nmol/mouse), which was mediated by DOR partially but not MOR. Conclusions: (1) Data indicated that MCRT was less prone to induce gastrointestinal dysmotility at analgesic doses, and provided a possibility for safer opioid analgesic. (2) Based on the mechanism explorations, we speculated on the existence of such an opioid receptor subtype or MOR/DOR heterodimer, which was involved in the central analgesia and the in vitro colonic contractions but not the central colonic dysmotility. Highlights: MCRT increased colonic contraction via μ- and δ- opioid receptors (MOR and DOR). MCRT delayed colonic bead expulsion independent of opioid and NPFF receptors. MCRT inhibited fecal number and dry weight mediated by DOR partially but not MOR. MCRT decreased gastrointestinal motility with higher dose than that used in analgesia.